Tpm implementation impact in companies´s competitivity in the metropolitan region of aburra’s valley and near east (2012)
Best practices methodologies have been used by different companies as competitive growing tools in a globalized market. In Colombia, particularly at Aburra’s Valley Metropolitan Area (AMVA) and near east can be noticed that TPM (Total Productive Management) had been adopted as a competitive support tool. This article evaluates the TPM implementation impact in different competitiveness variables for the companies that are working on it at the AMVA and near east, finding that there is not a clear relation between the accomplished improvements and the main returns, efficiency and overdue relations, even of the results obtained in key business indicators as OEE (Overall Equipment Effectiveness), failures (Breakdowns) and throughput.